Analisis systematic literature review Tafsir Tarbawi: implementasi Tafsir Tarbawi pada pendidikan Islam - Alwizar Alwizar; Syafaruddin Syafaruddin; Nurhasnawati Nurhasnawati; Darmawati Darmawati; M. Fahli Zatrahadi; Hakmi Wahyudi; Istiqomah Istiqomah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
In addition to the ever-changing conditions, Islamic education faces increasingly complex obstacles. The digital era shows that the implementation of tarbawi interpretation in Islamic education can provide great benefits to students and society. The purpose of this study is to analyze the implementation of tarbawi interpretation in Islamic education in 2021. The research method used is a systematic literature review. Data from the scopus database is considered primary data, while data from the dimensions database is considered secondary data. The data obtained were 110 in the Scopus database and 8 documents in Dimensions. In the analysis, however, only 20 documents were included in the criteria. Research results suggest that the implementation of tarbawi interpretation in education is an obstacle. These challenges include limitations in understanding, social change, technological advancement, controversy, language barriers, and a lack of support from educational institutions and society.